Standardless semi-quantitative analysis by PIXE - Rodriguez Cabello, Tabatha Pamela (2017)
A method based on the refinement of atomic and experimental parameters developed for the description of PIXE spectra is presented and applied to standardless semi-quantitative PIXE analysis. This method was implemented in the sofware PAMPA (Parameter Assessment Method for PIXE Analysis) and consists in minimizing the quadratic differences between an experimental spectrum and an analytical function proposed to describe it. The first results of PAMPA are presented for the quantification of synthetic and mineral, thin and bulk samples, and they are compared with the results obtained with a commercial software.